Propuesta PADALÚV para desarrollar el periodo de adaptación en niños de 3 años del jardín público, Víctor Larco-2021 - Cabrera Esquivel, Hellen Brigitte (2023)
The present investigation titled PADALÚV Proposal to develop the adaptation period in 3- year-old children in a public garden, Víctor Larco-2021. Its purpose was to improve the adaptation period in the 3-year-old boys and girls of the public garden, through an educational program based on virtual recreational activities. The research was basic descriptive proposition, where we have described the observed reality; it was carried out with a sample of 10 children from the flexible green 3- year-old classroom of I.E 224 Indoamérica, made up of 4 boys and 6 girls. Obtaining as a result that 90% of the children are at a low level and 10% at a medium level, demonstrating the elaboration of the instrument of the PADALÚV proposal for the development of the adaptation period.